1983
DOI: 10.1111/j.1095-8649.1983.tb04219.x
|View full text |Cite
|
Sign up to set email alerts
|

Observations on the dietary habits of wild and stocked brown trout, Salmo trutta L., in Irish lakes

Abstract: The dietary habits and feeding rates of wild and stocked brown trout were compared for populations in a number of Irish lakes. Wild trout and stocked fish, which had been present in a fishery for 12 months or longer, tend to feed on the same dietary items at similar rates.Stocked fish in their immediate post-planting period (1-14 days) ate less than both the wild trout and established planted fish. In some instances recently stocked fish appear to have a preference for surface food items. They also consumed st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
1
1

Year Published

1990
1990
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 15 publications
(9 reference statements)
2
30
1
1
Order By: Relevance
“…However that is clearly not the case in the current study where there was only one fish per cage. This lower than expected stomach fullness may be representative of a hatchery (rather than wild) fish model since other studies also indicate that it is common for hatchery fish released into the wild to initially have less material in their digestive system than expected (Sosiak et al 1979, Myers 1980, O'Grady 1983, Johnsen and Ugedal 1986, Hvidsten 1994, Fjellheim et al 1995.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…However that is clearly not the case in the current study where there was only one fish per cage. This lower than expected stomach fullness may be representative of a hatchery (rather than wild) fish model since other studies also indicate that it is common for hatchery fish released into the wild to initially have less material in their digestive system than expected (Sosiak et al 1979, Myers 1980, O'Grady 1983, Johnsen and Ugedal 1986, Hvidsten 1994, Fjellheim et al 1995.…”
Section: Discussionmentioning
confidence: 77%
“…Other laboratory studies (Maynard et al 1996a, Paszkowski andOlla 1985), and many field studies (Ersbak and Haase 1983, Miller 1952, Hochachka 1961, Reimers 1963, Sosiak et al 1979, Myers 1980, O'Grady 1983, Johnsen and Ugedal 1986 have found that hatchery fish starve for several weeks after release. In the natural environment the fish are experiencing very different water sources, physical conditions (gravel, vegetation, overhead cover, temperature, sounds, and light levels), predators, and many other animals they never previously encountered.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Selon CRESWELL (1981) et O'GRADY (1983 les mortalités hivernales liées en partie au manque de nourriture pourraient être un des facteurs explicatifs des différences observées entre les relâchers (1975( ) et O'GRADY (1984 qui ont mis en évidence la faible survie hivernale ( < 26%) des O"*" de fario et TAC dans les lacs irlandais. Par ailleurs selon O'GRADY (1983) les truites d'élevage récemment déversées mangent moins que les truites sauvages, utilisent peu la faune benthique au début et préfèrent la nourriture de surface.…”
Section: Discussion-conclusionunclassified